The Practicality of Popular Scientific Books based on the Diversity of Fish Species in Puting River Waters - Iim Mahayu Buana Kusuma Rini; Muhammad Zaini; Danang Biyatmoko (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Teaching materials are needed to assist in the learning process. One of the teaching materials that can be used is in the form of popular scientific books. Popular scientific books developed must be based on local potential to support learning the concept of diversity in animal ecology courses. So the purpose of this development research is to get the results of the practicality of the contents and expectations of the prototype of a popular scientific book with the title